SELF-DIRECTED LEARNING (SDL) THROUGH MOBILE ASSISTED LANGUAGE LEARNING (MALL) IN LEARNING SPEAKING OUT-OF-CLASS: : THE USE OF DUOLINGO, CAKE, ELSA SPEAK, MODLY, AND BUSUU APPLICATION - Susinta Dwi Agustina; Nor Laili Fatmawati (Yavana Bhasha : Journal of English Language Education, 2024)
Nowadays, students need more time to improve speaking skill by learning speaking out-of-class using mobile application This research aims to analyze the process of students Self-Directed Learning (SDL) using Mobile Assisted Language Learning (MALL), and to identify the students’ reasons in using Mobile Assisted Language Learning (MALL) to build Self-Directed Learning (SDL) in supporting learning speaking out-of-class at UIN Raden Mas Said Surakarta in academic year 2022/2023. The research method applied descriptive qualitative method. The research collecting data used interview, and observation technique. The result of this research showed that semester students who used MALL have structured process of SDL which deals with; (a) The students determine learning need; (b) The students determine goals from their needs and define structured objectives to accomplish their goals using a mobile application; (c) The students choose learning materials on the mobile application; (d) The students do learning activity using mobile application; (e) The students evaluate their learning progress using mobile applications as their self-assessment; (f) The students reflect on their learning progress as their self-reflection. Then students’ reasons in using mobile application in learning speaking which deals with; (a) Mobile application is flexible in place; (b) Mobile application is flexible in time; (c) Mobile application has clear instruction, enjoyable, effective, and helpful in learning speaking; (d) Mobile application has features that can help students do speaking practice; (e) The English learning material is available in the application.